PCDH20 inhibits esophageal squamous cell carcinoma proliferation and migration by suppression of the mitogen-activated protein kinase 9/AKT/β-catenin pathway - Ning, Yijiao; Deng, Chaoqun; Li, Chunhong; Peng, Weiyan; Yan, Chun; Ran, Jing; Chen, Weihong; Liu, Yujia; Xia, Jiuyi; Ye, Lin; Wei, Zhengqiang; Xiang, Tingxiu (Frontiers in Oncology, 2022)
Aberrant Protocadherins (PCDHs) expression trigger tumor invasion and metastasis. PCDH20 anti-tumor functions in various tumor have been identified. Tumor suppression is due to Wnt/β-catenin pathway antagonism and may be suppressed caused by PCDH20 down-regulation through promotor methylation while PCDH20 effects and regulation mechanism in esophageal squamous cell cancer (ESCC) remains elusive. We analyzed PCDH20 effects on ESCC and underlying action mechanisms for PCDH20. We test PCDH20 expression in ESCC tissues and cells by real-time PCR and real-time quantitative PCR. MSP was carried out to assess methylation of PCDH20 in ESCC cells and tissues. Anti-tumor effects of PCDH20 in vitro were assessed by clone formation assay, CCK8 assay, Transwell assay and flow cytometry. Nude mice tumorigenicity was used to assess PCDH20 anti-tumor effect in vivo. Online database, qPCR, and western blotting were used to identify PCDH20 down-regulated messages associated with AKT/β-catenin signaling activation. We found PCDH20 expression was dramatically attenuated in esophageal cancer tissues and cells due to promotor methylation, and ectopic PCDH20 expression suppressed ESCC malignant biological phenotypes. PCDH20 exerted anti-tumor effects by MAP3K9 down-regulation, which suppressed AKT/β-catenin signaling in ESCC cells. Conclusion: PCDH20 was a tumor suppressor gene, which antagonized AKT/β-catenin signaling pathway in ESCC by decreasing MAP3K9.